Home schooling during the COVID-19 pandemic: An assessment of Malaysia's PdPR Program - Mohammad Niaz Asadullah (Asian Development Bank Institute (ADBI), 2022)
Governments around the world have introduced a variety of programs aimed at facilitating distance learning in the home setting during school closures due to COVID-19. However, given the cross-country variations in state capacity, these programs differ significantly in terms of design, delivery, and coverage. Between-country variations in poverty and home conditions also create added challenges for home schooling programs. Therefore case studies examining country-specific programs are necessary. To this end, this paper examines the Pengajaran dan Pembelajaran di Rumah (PdPR) in Malaysia, an uppermiddle-income country with high Internet coverage and a low level of extreme poverty. Data come from a purposefully designed nationwide social media survey on secondary school children conducted during January 2021. Under the PdPR scheme, the government created various technology-based platforms to ensure online learning. By way of studying children's participation in educational activities during school closures, this paper presents a descriptive assessment of the PdPR program. More specifically, we first develop a conceptual framework to summarize the PdPR initiative. Then we examine PdPR in three aspects: the regularity of online lessons offered by school authorities; the extent of the use of specific components and the medium of access of the PdPR scheme by learners; their subjective evaluation of, and difficulties faced with, online schooling. Data confirm a significant socioeconomic divide by income and location in access to EdTech as well as home support provisions. Most importantly, not only are online lessons irregular, but a significant proportion of students found online programs difficult to follow. Given the dissatisfaction, the majority prefer to return to on-site education once schools reopen.
Keywords: D10; I21; J22; Q50; 330; COVID-19; EdTech; learning crisis; home-based education; school closure